Peran Regulasi Pemerintah Terhadap Penjualan Mobil Listrik pada Agustus 2025 - Budiastuti, Dewi Retno; Sari, Ratna Kartika; Sembiring, Sanika (University of Prof. Dr. Moestopo (Beragama), 2025)
Current global industrial developments are faced with the limitations of fossil fuels and the increasing impact of global warming due to air pollution. In August 2025, Indonesia was recorded as one of the countries with the highest air pollution levels in the world, driving the urgency for the implementation of more environmentally friendly transportation. Battery Electric Vehicles (BEVs) have become a strategic solution supported by government policies. This study aims to analyze the role of government regulations in increasing electric car sales in Indonesia, particularly during the August 2025 period. The research method employed is a qualitative library research method with a descriptive approach, conducted through a review of academic literature, statutory regulations, industry reports, and electric vehicle sales data. The results indicate that government regulations in the form of fiscal and non-fiscal incentives—such as exemptions from Luxury Goods Sales Tax (PPnBM), Government-Borne Value Added Tax (PPN DTP) incentives, import duty exemptions, the development of Public Electric Vehicle Charging Station (SPKLU) infrastructure, and support for the electric vehicle industry and supply chain—have a significant impact on increasing electric car sales. Sales data showed consistent monthly and annual growth in August 2025. Nevertheless, challenges remain, particularly regarding import dependence and the fulfillment of the Domestic Component Level (TKDN). Overall, government regulations play a crucial role in accelerating the adoption of electric cars in Indonesia.